Case Report: A Peculiar Case of Inflammatory Colitis After SARS-CoV-2 Infection - Rutigliani, Mariangela; Bozzo, Matteo; Barberis, Andrea; Greppi, Marco; Anelli, Emanuela; Castellaro, Luca; Bonsignore, Alessandro; Azzinnaro, Antonio; Pesce, Silvia; Filauro, Marco; Rollandi, Gian Andrea; Castagnola, Patrizio; et al. (Frontiers in Immunology, 2022)
We report a case of inflammatory colitis after SARS-CoV-2 infection in a patient with no additional co-morbidity who died within three weeks of hospitalization. As it is becoming increasingly clear that SARS-CoV-2 infection can cause immunological alterations, we investigated the expression of the inhibitory checkpoint PD-1 and its ligand PD-L1 to explore the potential role of this axis in the break of self-tolerance. The presence of the SARS-CoV-2 virus in colon tissue was demonstrated by qRT-PCR and immunohistochemical localization of the nucleocapsid protein. Expression of lymphocyte markers, PD-1, and PD-L1 in colon tissue was investigated by IHC. SARS-CoV-2-immunoreactive cells were detected both in the ulcerated and non-ulcerated mucosal areas. Compared to healthy tissue, where PD-1 is weakly expressed and PD-L1 is absent, PD-1 and PD-L1 expression appears in the inflamed mucosal tissue, as expected, but was mainly confined to non-ulcerative areas. At the same time, these markers were virtually undetectable in areas of mucosal ulceration. Our data show an alteration of the PD-1/PD-L1 axis and suggest a link between SARS-CoV-2 infection and an aberrant autoinflammatory response due to concomitant breakdown of the PD-1/PD-L1 interaction leading to early death of the patient.